VIRTUAL ASSISTANT: A TOOL FOR HEALTH CO-PRODUCTION IN COPING WITH COVID-19. - Fabrizzio, Greici Capellari; de Oliveira, Lincoln Moura; da Costa, Diovane Ghignatti; Erdmann, Alacoque Lorenzini; Guedes dos Santos, José Luís (Texto & Contexto Enfermagem, 2023)
Objective: to describe the development of a virtual assistant as a potential tool for health co-production in coping with COVID-19. Method: this is an applied technological production research study developed in March and April 2020 in Ave stages: 1) literature review, 2) content definition, 3) elaboration of the dialog, 4) test of the prototype, and 5) integration with the social media page. Results: the literature review gathered diverse scientific evidence about the disease based on the Brazilian Ministry of Health publications and by consulting scientific articles. The content was built from the questions most asked by the population, in March 2020, evidenced by Google Trends, in which the following topics emerged: concept of the disease, prevention means, transmission of the disease, main symptoms, treatment modalities, and doubts. Elaboration of the dialog was based on Natural Language Processing, intentions, entities and dialog structure. The prototype was tested in a laboratory with a small number of user computers on a local network to verify the functionality of the set of apps, technical and visual errors in the dialog, and whether the answers provided were in accordance with the user's question, answering the questions correctly and integrated into Facebook. Conclusion: the virtual assistant proved to be a health education tool with potential to combat "Fake News". It also represents a patient-centered form of health communication that favors the strengthening of the bond and interaction between health professionals and patients, promoting co-production in health.